BEYOND COMPLIANCE: DISCIPLINE, FACILITIES, CREATIVITY, AND TEAMWORK AS JOINT DRIVERS OF EMPLOYEE PERFORMANCE - Yandra Rivaldo (Postgraduate Management Journal, 2025)
This study examines the joint and partial effects of work discipline, work facilities, creativity, and teamwork on employee performance at PT. Bakri Karya Sarana, a logistics and construction-equipment trading firm in Batam, Indonesia. Small and medium-sized trading enterprises in Indonesia's outer-island industrial zones face persistent human-resource constraints, yet the combined behavioral and structural drivers of employee performance in such firms remain under-researched relative to large corporates. A quantitative associative design was used, with a census of all 75 permanent employees as respondents. Data were collected through a structured Likert-scale questionnaire and analyzed using multiple linear regression in SPSS 23, following classical assumption testing. The results show that work discipline (t = 8.230; p = .000), work facilities (t = 3.020; p = .003), creativity (t = 2.865; p = .002), and teamwork (t = 3.246; p = .001) each have a positive and significant partial effect on employee performance, and the four variables jointly explain 85.0 percent of the variance in employee performance (R² = .850; F = 95.130; p = .000). Work discipline is the most dominant predictor (β = .512), followed by creativity (β = .210), work facilities (β = .221), and teamwork (β = .184). The findings indicate that performance in this firm rests primarily on behavioral compliance, reinforced by adequate physical infrastructure and a working culture that supports both individual initiative and collaboration, with implications for human-resource practice in comparable trading and logistics SMEs.